Basic Algebra

posted by .

solve the equation: 16((3x+7)=4(12x+8)

  • Basic Algebra -

    16(3x+7)=4(12x+8)

    48x + 112 = 48x + 32

    This problem doesn't have a solution.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. algebra2

    1/3 - 5/6 = 1/X SOLVE 1/3 - 5/6 = 1/X Let's remove the denominators by multiplying by 12X 12X*(1/3) - 12X*(5/6) = 12X*(1/X) Clear the fractions. 4X - 10X = 12 -6X=12 multipy by -1 6X=-12 Divide both sides by 6 6X/6 = -12/6 X = -2 Check …
  2. help...solving a polynomial....algebra

    solve this please....help me....12x(squared)+7x-10 Do you wish to factor this trinomial?
  3. Algebra

    I don't know how to solve 12x(2)-15x=0 using the quadratic equation ax+bx+c=0 with this question I am unsure of what a, b and c are supposed to be, therefore I do not know how to solve this! Please help!
  4. algebra

    solve the following equation by clearing fraction want to know if this right -7/3-5/2x=8+2x 6(-7/3)-(5/2)(6)=6(6)+2x(6) 14x-15=48+12x 14x-12x-15=48+14x-14x 2x-15=48 2x-15+15=48+15 2x=-33 2x/2x=-33/2 x=-33/2
  5. algebra

    solve the following equation by clearing fractions show all work want to know if this right -7/3-5/2x=8+2x 6(-2/3)-(5/2x)(6)=6(8)+2x(6) 14x-15=48+12x 14x-12x-15=48+14x-14x 2x-15=48 2x-15+15=48+14x-14x 2x-15=48 2x-15+15=48+15 2x=-33 …
  6. algebra 2

    Samantha needs to solve the equation x2 - 12x = 40. What must she do to each side of the equation to complete the square?
  7. algebra 2

    Samantha needs to solve the equation x2 - 12x = 40. What must she do to each side of the equation to complete the square?
  8. Algebra

    To solve 9x^2-12x+4=49 by using the Square Root Property, you would first rewrite the equation was as A. 9x^2-12x-45=0 B.(3x-2)^2=+/-49 C.(3x-2)^2=7 D.(3x^2)^2=49
  9. Algebra. Please check my answers

    Evaluate a/b+c^d for a=6,b=3,c=4 and d=5 A.42*** B.18 C.82 D.360 What is the simplified form of the expression ?
  10. Algebra

    What is the vertex form of the equation? y = -x^2+12x-4 My work: -(x^2 + 12x)-4 -(x^2 + 12x + 36)-4 + 36 Y= -(x+36)^2 + 32 Is this correct?

More Similar Questions